2008
DOI: 10.1515/zna-2008-7-818
|View full text |Cite
|
Sign up to set email alerts
|

Solvatochromic Study on Binary Solvent Mixtures with Ionic Liquids

Abstract: Solvent effects on 2,6-dichloro-4-(2,4,6-triphenyl-pyridinium-1-yl)phenolate [E T (33) dye] and 7-diethylamino-3,4-benzophenoxazine-2-one (Nile Red) in binary mixtures of organic solvents (acetone, acetonitrile, propylene carbonate, methanol and ethane-1,2-diol) with 1,3-dialkyl imidazoliumbased ionic liquids were studied by UV-visible spectroscopy. Highly nonlinear behaviour of mixtures of alcohols and ionic liquids was found. A preferential solvation model was applied to the data obtained on solvatochromic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Note, however, that the nonlinearity is substantially reduced when Φ IL is used as the composition variable. Similar composition dependence is observed in UV absorption shifts of the π* probe N , N -dimethyl-4-nitroaniline , in these mixtures, and in the probes phenol blue and Nile Red in the closely related [Im 41 ][PF 6 ] + CH 3 CN system. The departures from linearity in all of these cases might be interpreted as indicating the solute is preferentially solvated by [Im 41 ][BF 4 ].…”
Section: Resultssupporting
confidence: 72%
“…Note, however, that the nonlinearity is substantially reduced when Φ IL is used as the composition variable. Similar composition dependence is observed in UV absorption shifts of the π* probe N , N -dimethyl-4-nitroaniline , in these mixtures, and in the probes phenol blue and Nile Red in the closely related [Im 41 ][PF 6 ] + CH 3 CN system. The departures from linearity in all of these cases might be interpreted as indicating the solute is preferentially solvated by [Im 41 ][BF 4 ].…”
Section: Resultssupporting
confidence: 72%
“…Other applications have been found for the pyridinium N -phenolates involving solvent mixtures. Several studies have been carried out on these probes in binary mixtures of molecular solvents with ILs. ,,, Fletcher and Pandey reported the influence of water on the E T (30) values of [bmim] + [PF 6 ] − , observing that the solvatochromic CT band of dye 1 in the IL is hypsochromically shifted with the addition of water, increasing from E T (30) = 52.4 kcal mol –1 in the IL to 63.1 kcal mol –1 in pure water, corresponding to a Δλ max value of −93 nm (Δν̅ max = +3743 cm –1 ). The ability of the pyridinium N -phenolate dyes to reflect changes in the polarity of ILs in the presence of small amounts of water has been used for analytical purposes, to estimate the water content of ILs using vis spectrophotometric techniques and calibration curves. , An investigation of the polarity of binary mixtures of [bmim] + [PF 6 ] − with TFE using dye 1 revealed that these mixtures are strongly synergistic, an effect that has been referred to as hyperpolarity .…”
Section: Pyridinium N-phenolate Dyes In the Investigation Of Solvent ...mentioning
confidence: 99%
“…This nonlinear behavior could explain the occurrence of a minimum in excited-state relaxation time within this range of mixture composition and may be associated with changes in the interactions between the mixture components and the dye at low X IL values. With this respect, various properties of IL-MS mixtures show significant changes in this low X IL region. , Indeed, in this range of mole fractions, spectroscopic studies have reported noticeable changes in vibration modes and 1H NMR chemical shifts. Additionally, various chemical and physical properties, such as diffusion and conductivity, exhibit nonlinear changes dependent on the specific IL-MS mixtures.…”
Section: Resultsmentioning
confidence: 99%